Hidden factors the prospects for saving the tropical forests [videorecording]. - Palma, Ma. Tina Monzon ([S.l.] Pilipinas Shell Petroleum Corp., 1989)
Presents some insights and studies made on forest conservation.
Host, Ma. Tina Monzon Palma.
Keywords: Forests and forestry; Reforestation; Environmental science